Enabling Enduring Evidence-Based Policy for the Southern Ocean Through Cultural Arts Practices - Roberts, Lisa; Kutay, Cat; Melbourne-Thomas, Jess; Petrou, Katherina; Benson, Tracey M.; Fiore, Danae; Fletcher, Paul; Johnson, Ellery; Silk, Melissa; Taberner, Stephen; Filgueira, Victor Vargas; Constable, Andrew J. (Frontiers in Ecology and Evolution, 2021)
This paper provides a perspective on how art and cross-cultural conversations can facilitate understanding of important scientific processes, outcomes and conclusions, using the Marine Ecosystem Assessment for the Southern Ocean as a case study. We build on an increasing body of literature that identifies how Indigenous perspectives move us away from a strictly utilitarian approach in the present, to a more socially and globally aware approach for the future, one that is grounded in deep knowledge of the past as leading to the present and providing a path to see the future. First, we reflect our rationale and the need for deeper communication through the arts to be a part of the process for making decisions and engaging and obtaining perspectives from more than just a utilitarian lens. Second, we draw on the LivingData initiative which is using art in all its forms to bridge differences in knowledge systems and their values. It provides examples of how Indigenous knowledge and Western science can be complementary, and how Indigenous knowledge can show the difference between historical natural environmental phenomena and current unnatural phenomena, including how the Anthropocene is disrupting cultural connections with the environment that ultimately impact everyone. Our perspective is derived from a group with vastly different backgrounds, histories, knowledge systems and values. Lastly, we document the process of our experience and draw lessons from it on how deeper communication between us benefited the outcomes and purpose of LivingData and could benefit decision-making.